Long-term effects of pre-operative teaching and post-operative rehabilitation on post-operative adjustment of mastectomy and hysterectomy patients - Gloria, Myrna D.
Rehabilitation of a patient with cancer involves a complicated process, the aim of which is to restore the individual to a normal or near-normal state as possible, calling for the cooperative effort of the patient himself and the different health care givers. This study endeavors to formulate guidelines for an effective way of promoting optimum postoperative adjustment of female patients with cancer of the reproductive system (uterus/breast). The Department of Research of the University of the Philippines College of Nursing, jointly with the Department of Nursing Research and Development of the Philippine General Hospital conducted a study on several aspects of the postoperative adjustment of patients who have undergone mastectomy (for breast cancer) and hysterectomy in the University of the Philippines-Philippine General Hospital (UP-PGH) Medical Center. A portion of the study pertained to the long-term effects of a program of preoperative teaching and postoperative rehabilitation on the postoperative adjustment of patients measured at different time periods - immediate postoperative period, 1 month, 1 year, and 5 years after surgery. The scope of the study reported here covered the 1-month after follow-up of post-mastectomy and posthysterectomy patients. The main problem of the study is to find out whether a program of preoperative teaching and post-operative rehabilitation will promote optimum post-operative adjustment among postmastectomy and posthysterectomy patients at 1 month after surgery. The result of the study showed that: 1. The instructed subjects in both the post-mastectomy and posthysterectomy groups performed self-care activities at home significantly better than the uninstructed group. 2. Among the postmastectomy patients, there is a trend for the instructed group to have lesser number of preventable (or rehabilitative) type of complications than the instructed group. 3. Among the posthysterectomy patients, no remarkable differences were seen in the incidence of preventable complications in the instructed and uninstructed groups. 4. Differences in the postoperative behavior if the instructed and uninstructed groups for both the posthysterectomy and post-mastectomy groups were not statistically significant, although the mean scores of the control groups were higher (indicating a greater number and intensity of post-operative difficulties) than those of the experimental group. In conclusion the study points to the favorable effects of providing a program of preoperative teaching, discharge planning and postoperative rehabilitation to patients who undergo mastectomy and hysterectomy. There is still a need, however, to conduct follow up studies to demonstrate whether such favorable effects extends beyond the 1st month after surgery.
Thesis (Master of Arts in Nursing)--University of the Philippines Manila.
Keywords: Pre-operative teaching; Post-operative care; Hysterectomy patients; Mastectomy patients